Peripheral and Central Effects of Melatonin on Blood Pressure Regulation - Pechanova, Olga (Int J Mol Sci, 2014)
The pineal hormone, melatonin (N-acetyl-5-methoxytryptamine), shows potent receptor-dependent and -independent actions, which participate in blood pressure regulation. The antihypertensive effect of melatonin was demonstrated in experimental and clinical hypertension. Receptor-dependent effects are mediated predominantly through MT1 and MT2 G-protein coupled receptors. The pleiotropic receptor-independent effects of melatonin with a possible impact on blood pressure involve the reactive oxygen species (ROS) scavenging nature, activation and over-expression of several antioxidant enzymes or their protection from oxidative damage and the ability to increase the efficiency of the mitochondrial electron transport chain. Besides the interaction with the vascular system, this indolamine may exert part of its antihypertensive action through its interaction with the central nervous system (CNS). The imbalance between the sympathetic and parasympathetic vegetative system is an important pathophysiological disorder and therapeutic target in hypertension. Melatonin is protective in CNS on several different levels: It reduces free radical burden, improves endothelial dysfunction, reduces inflammation and shifts the balance between the sympathetic and parasympathetic system in favor of the parasympathetic system. The increased level of serum melatonin observed in some types of hypertension may be a counter-regulatory adaptive mechanism against the sympathetic overstimulation. Since melatonin acts favorably on different levels of hypertension, including organ protection and with minimal side effects, it could become regularly involved in the struggle against this widespread cardiovascular pathology.